The magnesium transporter A is activated by cardiolipin and is highly sensitive to free magnesium in vitro - Saranya Subramani; Harmonie Perdreau-Dahl; Jens Preben Morth (eLife, 2016)
The magnesium transporter A (MgtA) is a specialized P-type ATPase, believed to import Mg2+ into the cytoplasm. In Salmonella typhimurium and Escherichia coli, the virulence determining two-component system PhoQ/PhoP regulates the transcription of mgtA gene by sensing Mg2+ concentrations in the periplasm. However, the factors that affect MgtA function are not known. This study demonstrates, for the first time, that MgtA is highly dependent on anionic phospholipids and in particular, cardiolipin. Colocalization studies confirm that MgtA is found in the cardiolipin lipid domains in the membrane. The head group of cardiolipin plays major role in activation of MgtA suggesting that cardiolipin may act as a Mg2+ chaperone for MgtA. We further show that MgtA is highly sensitive to free Mg2+ (Mg2+free) levels in the solution. MgtA is activated when the Mg2+free concentration is reduced below 10 μM and is strongly inhibited above 1 mM, indicating that Mg2+free acts as product inhibitor. Combined, our findings conclude that MgtA may act as a sensor as well as a transporter of Mg2+.